The Portrait of Women Resistance Towards Patriarchy System in The Movie of Dilema Ijab Kabul - Suhadi, Suhadi (Universitas Negeri Semarang, 2015)
This paper aims to interpret the women resistance towards the patriarchy system on a documentary film entitled â€œDilema Ijab Kabulâ€. The focus of the documentary film analysis which portrays the behavior of early marriage is to be the earliest mapping in explaining that the action the women take is really as an opposition or vice versa. The concept used in analyzing the resistance of women against patrialkhal system in this documentary was the concept of the meaning of each daily interactions in society, womenâ€™s position, and orientation in a relation to men and women. Based on the finding, the analysis result of this documentary movie tries to invite the audience to see the wedding of the social phenomenon that is very different from the usual. Marriage is shown by a hegemony which then leads to a form of resistance from the women. Resistance to the patriarchy system which is done by women in the documentary movie is seen from many phenomenon of early marriage, divorce, and re-marry.Â